Antimicrobial resistance at the human–animal interface in the Pastoralist Communities of Kasese District, South Western Uganda - Iramiot, Jacob Stanley; Kajumbula, Henry; Bazira, Joel; Kansiime, Catherine; Asiimwe, Benon B. (Scientific Reports, 2020)
Intensive usage of antimicrobials in the management of animal diseases leads to selection for resistance among microorganisms. This study aimed to assess antimicrobial use and to describe factors associated with the transmission of antimicrobial resistance between humans and animals in pastoralist communities of Kasese district. A mixed-methods approach was employed in this study. Rectal swabs were collected from the participants and cattle and transported in Carry–Blaire transport medium to the laboratory within 24 h of collection for culture and sensitivity to confirm carriage of multi-drug resistant bacteria. In-depth interviews were conducted among veterinary officers, veterinary drug vendors, human health facility in-charges in both public and private health facilities, and operators of human pharmacies and drug shops. Carriage of multi-drug resistant bacteria among humans was 88 (93%) and 76(80%) among cattle. Consumption of lakeshore water and carriage of multi-drug resistant bacteria in cattle were associated with carriage of multi-drug resistant bacteria in the human population. The prevalence of multi-drug resistance among organisms Isolated from both humans and animals was high. There is a high likelihood of transmission of multi-drug resistance between humans and animals.
Keywords: Antimicrobial resistance; Human–animal interface; Pastoralist Communities; South Western; Uganda; Intensive usage